2014
DOI: 10.1007/s40139-014-0048-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Cholangiopathies

Abstract: Cholangiocytes, the cells lining bile ducts, comprise a small fraction of the total cellular component of the liver, yet perform the essential role of bile modification and transport of biliary and blood constituents. Cholangiopathies are a diverse group of biliary disorders with the cholangiocyte as the target cell; the etiopathogenesis of most cholangiopathies remains obscure. MicroRNAs are small non-coding RNAs that post-transcriptionally regulate gene expression. These small RNAs may not only be involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 86 publications
0
21
0
Order By: Relevance
“…The contribution of miRNAs in PLD pathogenesis was recently shown [66, 67]. MiRNA profiles are globally affected in cystic cholangiocytes with the majority of them being down-regulated.…”
Section: Therapeutic Targets In Pldmentioning
confidence: 99%
“…The contribution of miRNAs in PLD pathogenesis was recently shown [66, 67]. MiRNA profiles are globally affected in cystic cholangiocytes with the majority of them being down-regulated.…”
Section: Therapeutic Targets In Pldmentioning
confidence: 99%
“…Among these molecules, aberrant expression of miRNAs has received a great deal of attentions for its diagnostic and prognostic value in different kinds of human cancers, such as breast cancer, lung cancer, colorectal carcinoma, and hepatocellular cancer [32][33][34][35][36]. Steven et al [37] in summarizing recent studies on the role of miRNAs in CCA suggested that these miRNAs could be an important diagnostic and prognostic tool for CCA patients. Thus, the purpose of this study was to explore a novel functional miRNA for its value as a prognostic marker in CCA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue engineering approaches mimicking biliary function would require a more complex microarchitecture of scaffolds that enable cell-cell interactions, allowing for biliary metabolism and transport [213,214]. Although little is known about the role of miRNAs in regulating cholangiocyte proliferation and function [215], several studies implicated specific miRNAs in the pathogenesis of cholangiocarcinoma. For example, the overexpression of miR-31 in cholangiocarcinoma cells altered RAS/MAPK signaling [216], and miR-138 can regulate cholangiocarcinoma proliferation, cell-cycle control, and migration, possibly by directly targeting RhoC [217].…”
Section: Liver Tissue Engineeringmentioning
confidence: 99%